Galactic hail: the origin of the high-velocity cloud complex C - Fraternali, Filippo; Marinacci, Federico (Monthly notices of the Royal Astronomical Society. Letters, 2015)
Abstract. High-velocity clouds consist of cold gas that appears to be raining down from the halo to the disc of the Milky Way. Over the past 50 years, two comp